(3GdedNU (B((3edNU GdbhGfjf aj GdfMh(B)s - (3CHhGdMSjf YHjO Gddg Hf CMeO Hf YHjO Gddg GHf CHj GdQHjY GdbQTj GdCehj GdYKeGfj GdGTHjdj,J (B688 (3g` s
(3ChdgG (B:s
(3HGH GdVeGFQ(B: (3GdcdGe ajgG aj NeSI aUhd GdaUd GdChd aj YOOgG hgj SJhf VejQG s
(3BNQgG (B:s
(3hEOZGegG aj Gdfhf Cbd eeG PcQ, hEfeG bd dCf Gdfhf JOZe aj NeSI CMQa ceG JbOe s
(3fSNI KGdKI JJab aj BNQgG eY BNQ GdfSNI GdChdis
(3HgG Jda aj HYV SWhQ GdhQbI GdChdis
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B191s
Keywords: (3GdfMhs